Oxidation of H2, CO and syngas mixtures on ceria and nickel pattern anodes. (15th September 2015) - Patel, H.C.; Tabish, A.N.; Comelli, F.; Aravind, P.V.
Highlights: Pattern anodes of Nickel and Ceria on YSZ tested with CO, H2 and H2 /CO mixtures. Polarisation resistance with CO is higher than H2 on nickel and ceria pattern cells. Lower polarisation resistance obtained for CO oxidation on ceria compared to nickel. Lower activation energy on ceria indicates faster catalysis for CO oxidation. Preferential H2 oxidation on ceria and nickel pattern anodes in H2 –CO mixtures. Abstract: Understanding synthesis gas (syngas) oxidation on SOFC anodes is an important step towards commercialising SOFCs operating on realistic fuels. Using pattern anodes, we study electrochemical oxidation of H2 and CO on nickel and ceria pattern anodes with and without water. Further, H2 /CO mixtures are studied in dry and wet conditions. For all the compositions studied here, the polarisation resistance on ceria pattern anodes is lower than nickel pattern anodes indicating that the reaction zone is not limited to the three phase boundary. Also, in most cases the activation energy is also lower indicating ceria can be a superior catalyst. It is found that the polarisation resistance with CO is higher than that with hydrogen for both ceria and nickel pattern anodes. For wet CO mixtures there is a possibility that water gas shift reaction can play an important role. Addition of H2 brings about a dramatic decrease in the polarisation resistance in case of dry H2 /CO mixtures for both nickel and ceria pattern anodes. This indicates that hydrogen is preferentially oxidised so much so that it is possible that only hydrogen is oxidised with CO acting as a diluent.